ENVIRONMENTAL PERSONHOOD REIMAGINED: A CONCISE PHILOSOPHICAL REVIEW - Muhammad Pasha Nur Fauzan; Indra Perwira; Imamulhadi (Faculty of Law, Universitas Gadjah Mada, 2024)
Abstract This paper is built upon one question: can the natural world be recognised as a ‘member’ of a legal community? By exploring the nature of legal personhood, this paper revisits the concept of environmental personhood. This paper uses the naturalistic approach to ground legal philosophical analysis in empirical realities and gain a deeper understanding of the natural world. This paper argues that legal personhood is an institutional fact influenced by moral ideas configured based on how humans organise organize value. The concept of ‘environmental personhood’ is built upon the idea that the natural world possesses inherent rights that must be protected similarly to human rights. This paper finds that, although the ecocentric approach to environmental personhood must be rejected, it can be salvaged. By reformulating environmental personhood based on artificial personhood, this paper opens up opportunities for the concept to be maintained. It aims to ground a theoretical foundation for further constitutional law research, specifically regarding how the constitution should frame the natural world’s ideal position within the state. Abstrak Penelitian ini didasarkan pada satu pertanyaan: dapatkah lingkungan dimasukkan sebagai anggota komunitas hukum? Dengan menelusuri konsep subjek hukum, penelitian ini meninjau kembali konsep lingkungan sebagai subjek hukum. Artikel ini menggunakan pendataan filsafat hukum naturalistik guna mendasarkan analisis filsafat hukum pada realitas empiris dan mampu menangkap pemahaman lebih dalam mengenai realitas alam. Artikel ini menemukan bahwa subjek hukum merupakan fakta institusional yang dibentuk oleh gagasan moral, yang dikonfigurasikan berdasarkan cara manusia mengorganisasikan nilai. Konsep lingkungan sebagai subjek hukum didasarkan pada gagasan bahwa alam memiliki hak inheren yang harus dilindungi. Artikel ini juga menemukan bahwa, meski pendekatan ekosentris dalam konstruksi lingkungan sebagai subjek hukum inkoheren dan mesti ditolak, konsep tersebut mungkin masih dapat diselamatkan. Penelitian ini diharapkan dapat menyediakan fondasi teoritis untuk penelitian Hukum Tata Negara lanjutan, utamanya mengenai bagaimana konstitusi harus mengonstruksikan posisi realitas alam dalam negara.